Obesity and male infertility - Hamad Zubi, Zainab Bubakr; Alfarisi, Hamad; Ibrahim, Muhammad (Academy for Environment and Life Sciences, 2021)
Obesity is an excessive accumulation of fat in the human body to the level that adversely affects his health. The increase in infertility cases occurs in parallel with the increase in the prevalence of obesity. A common finding in several previous studies is the inverse relationship between body mass index and male fertility. Obesity correlates negatively with semen volume, total sperm count, sperm concentration, vitality, normal morphology and motility. It increases sperm with DNA fragmentation. Obesity also reduces inhibin B and testosterone, elevates leptin and serum oestrogens, alters prolactin secretion and suppresses hypothalamic-pituitary-gonadal axis. The increase in the prevalence of obesity calls for greater awareness of its effects on male fertility, better understanding of underlying pathophysiology, and determination of suitable treatment